Dislocation after total knee arthroplasty - Wazir, N.N.; Shan, Y.; Mukundala, V.V.; Gunalan, R. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2007)
Two cases of dislocation of total knee arthroplasty presented to us within the same week. The first patient is a 71-year-old woman who underwent bilateral primary total knee arthroplasty. The left knee dislocated three weeks after the surgery. Due to failure of conservative measures, she underwent revision total knee arthroplasty. The other patient is a 72-year-old woman presenting ten years after primary total knee arthroplasty, with a traumatic dislocation of the knee joint. She was treated as an outpatient with closed manipulative reduction.